Some Functional Properties of khambir, an Ethnic Fermented Cereal-Based Food of Western Himalayas - Hor, Papan K.; Ray, Mousumi; Pal, Shilpee; Ghosh, Kuntal; Soren, Jyoti P.; Maiti, Smarajit; Bera, Debabrata; Singh, Somnath; Dwivedi, Sanjay; Takó, Miklós; DasMohapatra, Pradeep K.; Mondal, Keshab C. (Frontiers in Microbiology, 2019)
Traditional leavened wheat-based flat bread khambir is a staple food for the high-altitude people of the Western Himalayan region. The health promoting abilities of two types of khambir, yeast added khambir (YAK) and buttermilk added khambir (BAK), were evaluated. A group of microbes like yeast, mold, lactic acid bacteria (LAB), and Bifidobacterium sp. were abundant in both khambir but in varied proportions. Both are enriched with phenolics and flavonoids. The aqueous extracts of both breads strongly inhibited the growth of enteropathogens. Molecular docking experiments showed that phenolic acid, particularly p-coumaric acid, blocked the active sites of β-glucosidase and acetylcholine esterase (AChE), thereby inhibiting their activities. YAK and BAK showed antiradical and antioxidant activity ranging from 46 to 67% evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), and ferric reducing/antioxidant power (FRAP) assays. The aqueous extract of both khambir samples protected the arsenic toxicity when examined under an in situ rat intestinal loop model study. The arsenic induced elevated levels of superoxide dismutase (SOD), catalase (CAT), reduced glutathione, lipid peroxidation (LPO) and DNA fragmentation, and transmembrane mitochondrial potential was alleviated by khambir extract. These results scientifically supported its age-old health benefit claims by the consumer at high altitude and there are enough potentialities to explore khambir as a medicinal food for human welfare.